INTEGRATED DEVELOPMENT OF LISTENING, SPEAKING, READING, AND WRITING SKILLS IN EFL LEARNERS (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
The integrated development of the four language skills—listening, speaking, reading, and writing—has become a central principle in modern English as a Foreign Language (EFL) pedagogy. Rather than treating skills as isolated components, contemporary approaches emphasize their interdependence in authentic communication. This article examines theoretical perspectives, cognitive and communicative foundations, pedagogical benefits, classroom implementation strategies, and assessment practices related to integrated-skill instruction. The study argues that combining receptive and productive skills within meaningful tasks promotes deeper language processing, stronger retention, and improved communicative competence. Challenges and practical solutions for effective integration are also discussed.